Innovations in Multistakeholder Partnerships for Sustainable Development: Fostering State–University–Community Nexus - Shaban, Abdul; Narnaware, Prashant B. (People-Centered Social Innovation, 2019)
This chapter shows that there is a possibility of fostering an enabling and innovative multistakeholder partnership for creating sustainable impact and transformative change with local communities. It argues that the collaborative efforts among district administration, educational institutions and civil society groups in supporting innovation and entrepreneurship can play an extremely important role in livelihood security and empowerment of marginalized sections. The chapter outlines the transformation of a marginalized and underdeveloped district of India. It presents a background of the district with a focus on farmers’ distress and discusses the mode of organization of elites and marginalized peoples under welfare and neoliberal regimes. The chapter also outlines the impact that state–university engagement on the communities. The neoliberal regime made the elite-based cooperatives ineffective, as they came under mismanagement and overexploitation by those in power. Neoliberal reform introduced a new vulnerability among Indian farmers, especially in certain states, such as Maharashtra.
Keywords: Asie; Réservé UdeM; Rôle des universités